The bonesetter's daughter - Tan, Amy. (New York : Ballantine, 2002)
San Francisco ghostwriter Ruth Young finally begins to understand her Alzheimer's-afflicted mother LuLing's preoccupation with ghosts and curses when she reads Luling's writings of her dark backwoods childhood in 1920s China--where LuLing's mute, disfigured nursemaid committed suicide, and a nearby cave held what may have been the bones of the lost ancient hominid Peking Man.
Booklist starred.
Library Journal.
Wilson's Fiction.
Adult
Keywords: Chinese American families -- Fiction; Chinese American women -- Fiction; Mothers and daughters -- Fiction; Women immigrants -- Fiction; Women -- China -- Fiction; Chinese American families -- Fiction; Chinese American women -- Fiction; Domestic fiction; Immigrants -- Fiction; Mother-daughter relationship -- Fiction; Women -- China -- Fiction; China -- Fiction; China -- Fiction